Enabling the Disabled: The Case of a Social Project - Al Abbasi, Sadin Naser (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Most young adults or adolescents with Down syndrome stay at home after the age of 18. Educational centers and rehabilitation centers in Jordan do not accept individuals with Down syndrome above 18 years. The objective of the study is to conduct a finan-cial analysis using capital budgeting techniques to understand if the project is finan-cially feasible and profitable or not. The project is an educational center that is aimed to help young adults with Down syndrome some skills that help them engage in the real life and make them feel included. The methods used in the study were Net Present Value (NPV), Discounted Payback Period, Internal Rate of Return (IRR), and Sensi-tivity analysis. The data used in the study was gathered from sources such as the World Bank, educational center in the same field in Jordan, and the water and electricity min-istries. The projected resulted with an NPV of 47,861.03 JD and an IRR of 16%. The sensitivity analysis tests the financial feasibility of the project under different scenarios to give a glimpse of what the future holds and a chance to take precaution may. The project was able to show good indications of financial feasibility. However, the risks may be high if some circumstances change. For the risk, a sensitivity analysis was done on the most effective parameters, which were the number of students, the fees charged, the salaries paid, and the rent paid. A change in these parameters whether negative or positive impacted the financial feasibility of the project. Keywords: Down Syndrome, Capital Budgeting, Net Present Value (NPV), Internal Rate of Return (IRR), Discounted Payback Period, Sensitivity Analysis.

ÖZ: Down sendromlu genç yetişkinlerin veya ergenlerin çoğu 18 yaşından sonra evde kal-maktadır. Ürdün'deki eğitim merkezleri ve rehabilitasyon merkezleri 18 yaşın üzerin-deki Down sendromlu bireyleri kabul etmemektedir. Çalışmanın amacı, projenin fi-nansal olarak uygulanabilir ve karlı olup olmadığını anlamak için sermaye bütçeleme tekniklerini kullanarak bir finansal analiz yapmaktır. Proje, Down sendromlu genç yetişkinlere gerçek hayata katılmalarına ve kendilerini dahil hissetmelerini sağlayacak bazı beceriler kazandırmayı amaçlayan bir eğitim merkezidir. Çalışmada kullanılan yöntemler Net Bugünkü Değer (NPV), İndirimli Geri Ödeme Süresi, İç Getiri Oranı (IRR) ve Duyarlılık analizidir. Çalışmada kullanılan veriler, Dünya Bankası, Ürdün'de aynı alandaki eğitim merkezi, su ve elektrik bakanlıkları gibi kaynaklardan top-lanmıştır. Öngörülen projenin 47,861,03 Ürdün dinarı NPV ve % 16 IRR ile sonuçlandı. Bu bulgular projenin uygulanabilir ve karlı olduğunu göstermektedir. Duyarlılık analizi, geleceğin neler getireceğine dair bir fikir vermek ve risklere karşı önlem alma için projenin finansal fizibilitesini farklı senaryolar altında test eder. Proje, mali fizibilite konusunda iyi göstergeler göstermeyi başardı. Bununla birlikte, bazı koşullar değişirse riskler yüksek olabilir. Risk için öğrenci sayısı, alınan ücretler, ödenen maaşlar ve ödenen kira gibi en etkili parametreler üzerinde bir duyarlılık ana-lizi yapılmıştır. İster olumsuz ister olumlu olsun, bu parametrelerdeki bir değişiklik, projenin finansal fizibilitesini etkiledi. Anahtar Kelimeler: Down Sendromu, Sermaye Bütçelemesi, Net Bugünkü Değer (NPV), İç Getiri Oranı (IRR), İndirimli Geri Ödeme Süresi, Duyarlılık Analizi.
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2020. Supervisor: Prof. Dr. Mustafa Besim.
Keywords: Banking and Finance; Projects--Financial Analysis; Down Syndrome; Capital Budgeting; Net Present Value (NPV); Internal Rate of Return (IRR); Discounted Payback Period; Sensitivity Analysis